Critical Insights: Film - Casablanca / James Plath - Plath, James
Considered one of the greatest films of the twentieth century, Casablanca earned three Academy Awards (including Best Picture) and instant critical and commercial success following its release in 1942. This inaugural volume in the Critical Insights Film series contains insightful essays analyzing the reasons for this film classic's acclaim, as well as its influences on the film industry as we know it today.